The Potential of Waqf and Zakat–Infaq–Sadaqah (ZIS) in Promoting Sustainable Economic Growth Across Indonesian Provinces (2021–2023) - Raden Ajeng Entaresmen; Nuraini Chaniago; Windhy Puspitasari; Risa Nurmala Dewi; Azizah Amelia Eka Susanti; Suryani; Itang (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
This study examines whether Waqf, Zakat and Infaq/Sadaqah actually promote sustainable economic growth in Indonesia, or whether this is merely an assumption. The 2021–2023 period was not chosen at random: this is the post-pandemic recovery period when inter-provincial disparities in the collection and distribution of Islamic social funds are most evident, and simultaneously the implementation period of the 2020–2024 National Medium-Term Development Plan (RPJMN), which provides verifiable SDG benchmarks. Secondary data from 35 provinces were analysed using panel regression. The results were mixed. Zakat and Infaq/Sedekah were found to have a positive and significant impact on social welfare and poverty alleviation. Wakaf, however, showed the opposite trend — a negative relationship with development indicators — which points more to governance issues than to weaknesses in the instrument itself. The direct implication is that the management of Wakaf needs to be institutionally reformed, rather than merely expanded. Meanwhile, the existing distribution mechanisms for Zakat and Infaq/Sedekah need to be maintained and strengthened. This study fills an empirical gap that has been largely overlooked in the literature on Islamic social finance, namely the differences in impact across provinces at the regional level.